Coronary artery lesions in children with Kawasaki disease: status quo and nursing care - Chen, Cen; Chen, Qiuhui; Zhang, Tong; Ling, Yanping (Frontiers in Cardiovascular Medicine, 2024)
Aim: Coronary artery lesion (CAL) is a common yet serious complication in children with Kawasaki disease. This study aimed to evaluate the influencing factors of CAL in children with Kawasaki disease, to provide reference for the clinical treatment and care of children with Kawasaki disease. Design: A retrospective cohort. Methods: Children with Kawasaki disease treated in a tertiary hospital of China from January 1, 2021 to December 31, 2022 were selected. The characteristics and clinical data of children with Kawasaki disease were analyzed. Spearman correlation analysis was conducted to evaluate the relationship of CAL and characteristics of children with Kawasaki disease. Logistic regression analysis was used to analyze the influencing factors of CAL in children with Kawasaki disease. Results: 185 children with Kawasaki disease were included, the incidence of CAL in children with Kawasaki disease was 18.38%. Pearson correlation analysis showed that gender(r=0.504), age(r=0.611), duration of fever ≥10 days(r=0.579), hemoglobin (Hb)(r=0.623) and C-reactive protein (CRP) (r=0.558) were all correlated with the CAL in children with Kawasaki disease (all p<0.05). Logistic regression analyses showed that male(OR=2.543, 95%CI: 1.801 3.077, p=0.040), age≤2 y(OR=3.002, 95%CI: 2.744 3.641, p=0.012), duration of fever ≥10 days(OR=2.089, 95%CI: 1.624 2.515, p=0.028), Hb ≤105 g/L(OR=1.914, 95%CI: 1.431 2.406, p=0.013), CRP≥100 mg/L(OR=2.168, 95%CI: 1.893 2.531, p=0.035) were the risk factors of CAL in children with Kawasaki disease (all p<0.05). Conclusions: The incidence of CAL in children with Kawasaki disease is high and there are many related risk factors. Clinical medical workers should take early warning and carry out interventions and nursing care according to these risk factors to improve the prognosis of children with Kawasaki disease.